Features of perfectionism and narcissism correlation - Anna V. Pushkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article describes the correlation between normal and pathological perfectionism with different types of narcissism. Researchers of these phenomena found a lot of related features of these phenomena, however, conducted studies of perfectionism and narcissism shows contradiction: in one study was a direct correlation between these phenomena, other studies have not received the link between perfectionism and narcissism. We have found that the pathological perfectionism is more familiar with the destructive narcissism, less to the deficit. Therefore, pathological perfectionism is more linked with the distortion of the relationship to itself, rather than lack of ability to form coherent and self-to generate a different view of themselves. The higher in the structure of the individual normal perfectionism, the more positive the individual presents himself, is able to rely on your positive experience. On the basis of the relationship it has been suggested on the period and the reason for the formation of pathological perfectionism: the period of formation of pathological perfectionism matches preedipal period, formed as a result of violation of a symbiotic relationship.